A mathematical modelling study of fluid flow and mixing in gas stirred ladles - Cloete, Schalk Willem Petrus (Stellenbosch : Stellenbosch University, 2008)
Thesis (MScEng (Process Engineering))--Stellenbosch University, 2008.